2016
DOI: 10.1681/asn.2015070745
|View full text |Cite
|
Sign up to set email alerts
|

Moss-Produced, Glycosylation-Optimized Human Factor H for Therapeutic Application in Complement Disorders

Abstract: Genetic defects in complement regulatory proteins can lead to severe renal diseases, including atypical hemolytic uremic syndrome and C3 glomerulopathies, and age-related macular degeneration. The majority of the mutations found in patients with these diseases affect the glycoprotein complement factor H, the main regulator of the alternative pathway of complement activation. Therapeutic options are limited, and novel treatments, specifically those targeting alternative pathway activation, are highly desirable.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
63
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 46 publications
(67 citation statements)
references
References 74 publications
(96 reference statements)
3
63
0
Order By: Relevance
“…A previously reported careful comparison between plasma-purified versions of V62-CFH and I62-CFH provided a benchmarking opportunity ( 22 ). Our yields of recombinant V62-CFH and I62-CFH exceeded those of previous attempts to produce CFH in mammalian ( 33 ), insect ( 34 ), and moss cells ( 35 , 55 ). Our versions of V62-CFH and I62-CFH differ in sequence at position 936 as well as at position 62 ( i.e.…”
Section: Discussionmentioning
confidence: 53%
“…A previously reported careful comparison between plasma-purified versions of V62-CFH and I62-CFH provided a benchmarking opportunity ( 22 ). Our yields of recombinant V62-CFH and I62-CFH exceeded those of previous attempts to produce CFH in mammalian ( 33 ), insect ( 34 ), and moss cells ( 35 , 55 ). Our versions of V62-CFH and I62-CFH differ in sequence at position 936 as well as at position 62 ( i.e.…”
Section: Discussionmentioning
confidence: 53%
“…74 Data on recombinant glycosylation-optimized full-length FH produced in moss and injected intravenously suggested serum t 1/2 of minutes rather than hours. 75 In this context, both homodimeric mini-FH constructs possess markedly improved serum t 1/2 compared with FH 1-5^18-20 ( Figure 5A) and ability to restore plasma C3 levels. Thus, as with the in vitro fluid-phase assay, FH 1-5^18-20^R1-2 was most effective in restoring normal complement function in vivo.…”
Section: Discussionmentioning
confidence: 91%
“…In order to test whether heterosplicing is a common phenomenon in P. patens upon transgene expression, we analyzed already existing recombinant human complement factor H (FH)-producing moss lines 40 . Our RT-PCR analysis revealed that expression of the human FH CDS in moss generated two transcript variants, the full-length FH transcript of 3,639 bp and a 1,215 bp FH variant, which could lead to a truncated FH isoform with a molecular mass of 45.6 kDa ( Supplementary Fig.…”
Section: Splicing Of Fh Mrna Like Fix Occurs In Transgenic Plantsmentioning
confidence: 99%
“…The first moss-made drug candidate, moss-aGal for enzyme replacement therapy of Fabry disease, has successfully completed phase I clinical trials 38 . Additionally, a variety of other potential biopharmaceuticals is being produced in moss [39][40][41] .…”
Section: Introductionmentioning
confidence: 99%